Reproducing Kernel Method for Solving Nonlinear Fractional Fredholm Integrodifferential Equation. (2nd December 2018) - Kashkari, Bothayna S. H.; Syam, Muhammed I.
Abstract : This article is devoted to both theoretical and numerical studies of nonlinear fractional Fredholm integrodifferential equations. In this paper, we implement the reproducing kernel method (RKM) to approximate the solution of nonlinear fractional Fredholm integrodifferential equations. Numerical results demonstrate the accuracy of the present algorithm. In addition, we prove the existence of the solution of the nonlinear fractional Fredholm integrodifferential equation. Uniformly convergence of the approximate solution produced by the RKM to the exact solution is proven.